Decision-making Strategies and Professional Satisfaction of Nurses Working in Ear Nose Throat Clinics - Kaya, Nurten; Bolol, Nurper; Turan, Nuray; Kaya, Hatice; İşçi, Çiğdem (Fırat University, 2011)
Objective: This research was carried out to investigate relationship between the decision-making strategies and professional satisfaction of nurses working in Ear Nose Throat (ENT) clinic, and relationship between the personal-professional features. Materials and Methods: This cross-sectional study was conducted with 78 nurses selected to disproportionately group sampling method (78% of the universe). Approval of the institution and informed consent was obtained from patients before the start of the study. Data were obtained with Nurse Information Form, Professional Satisfaction Scale and Decision-Making Strategies Scale. Results: Almost all of the nurses were female (97.4%), the average age of 33.50, the Professional Satisfaction Scale score of 65.09 points (potential distribution is 20-100). In the Decision-Making Strategies Decision Scale (potential distribution of all sub-scale scores are 10-40); Internal Responce was 22.56, Logical Decision was 27.21, Dependent Decision was 20.88, Unstable Decision was18.95.There was statistical significance between age of nurses, vocational education, experience of work, work unit, task, voluntary selection and desire to leave of the ENT clinic with variables of Decision-Making Strategies Sub-Scales and/or Professional Satisfaction Scale scores. Also statistical significance was found between the Dependent Decision Sub-Scale scores with Career Decision Scale and Unstable Satisfaction Scale scores. Conclusion: Considering factors affecting the decision-making strategies, and professional satisfaction of nurses, autonomy should be provided, team work should be supported and so that professional satisfaction should be increased.

Amaç: Bu araştırma, Kulak Burun Boğaz (KBB) kliniğinde çalışan hemşirelerin karar verme stratejileri ve mesleki doyumlarını, bireysel-mesleki özellikler ve aralarındaki ilişki yönünden incelemek amacı ile yapılmıştır. Gereç ve Yöntemler: Kesitsel türdeki bu araştırma, oransız küme örnekleme yöntemi ile seçilen 78 hemşire (evrenin %78'i) ile gerçekleştirilmiştir. Araştırmaya başlamadan önce kurumlardan ve hemşirelerden bilgilendirilmiş onam alınmıştır. Veri toplama aracı olarak Hemşire Tanıtım Formu, Karar Verme Stratejileri Ölçeği ve Mesleki Doyum Ölçeği kullanılmıştır. Bulgular: Hemşirelerin hemen hemen hepsinin kadın (%97.4), yaş ortalamasının 33.50, potansiyel puan dağılımı 20-100 olan Mesleki Doyum Ölçeği puan ortalamasının 65.09, tüm alt boyutlarında potansiyel puan dağılımı 10-40 olan Karar Verme Stratejileri Ölçeğinin puan ortalamalarının ise İçtepisel Kararda 22.56, Mantıklı Kararda 27.21, Bağımlı Kararda 20.88, Kararsız Kararda 18.95 olduğu görülmüştür. Hemşirelerin yaş, mesleki eğitim durumu, mesleki ve birimdeki deneyim yılı, çalıştığı birim, çalışma şekli, görevi, KBB kliniğini isteyerek seçme durumu ve bu klinikten ayrılma isteği değişkenlerine göre Karar Verme Stratejileri Alt Ölçekleri ve/veya Mesleki Doyum Ölçeği puanları arasında istatistiksel anlamlılık taşıyan farkların olduğu belirlenmiştir. Ayrıca Bağımlı Karar Alt Ölçeği puanları ile Kararsız Karar Alt Ölçeği ve Mesleki Doyum Ölçeği puanları arasında istatistiksel anlamlılık taşıyan ilişkiler bulunmuştur. Sonuç: Hemşirelerin karar verme stratejilerini ve mesleki doyumlarını etkileyen etmenler göz önüne alınarak mesleki otonomları sağlanmalı, ekip çalışmaları desteklenmeli ve böylece mesleki doyumları artırılmalıdır.
Kulak Burun Boğaz Kliniklerinde Çalışan Hemşirelerin Karar Verme Stratejileri ve Mesleki Doyumları